Pelarangan Penggunaan Ban Kapten Pelangi (Onelove) Atau LGBT+ (Lesbian, Gay, Bisexual, Transgender, & Queer) Oleh Qatar Pada Pertandingan Sepak Bola Piala Dunia Tahun 2022 - Sulistiawan, Heri; Hidayah, Nikmatul (Kajian Hubungan Internasional, 2024)
The hosting of the 2022 FIFA World Cup in Qatar drew global attention, not only for the matches but also for the social and cultural policies implemented by the host nation. One of the most controversial policies was the ban on the use of rainbow armbands symbolizing support for the LGBTQ+ (Lesbian, Gay, Bisexual, Transgender, & Queer) community. This study analyzes the policy of banning the use of rainbow (OneLove) or LGBTQ+ (Lesbian, Gay, Bisexual, Transgender, & Queer) armbands during the 2022 World Cup by Qatar using John Spanier's theory of national interest with a qualitative descriptive research method. The analysis of the policy issued by Qatar is part of an effort to achieve its national interests. Qatar's national interests in this regard include the pursuit of national security, national prestige, and the protection and promotion of ideology. Although this policy is based on efforts to achieve national interests, particularly preserving the traditional values of the host nation, its implementation has sparked various global debates regarding the rights to freedom of expression and inclusivity in sports. Keywords : Armband, LGBTQ+, Qatar, 2022 World Cup